2021
DOI: 10.1029/2021jd034564
|View full text |Cite
|
Sign up to set email alerts
|

Gentle Topography Increases Vertical Transport of Coarse Dust by Orders of Magnitude

Abstract: Dust particles emitted in the atmosphere are responsible for numerous phenomena of global consequence here on Earth. In particular, coarse dust (with diameter greater than 5 μm) absorbs shortwave and longwave radiation which contributes to warming of the planet (Kok et al., 2017), redistributes mineral nutrients such as iron and phosphates to ocean (Jickells et al., 2014) and land ecosystems (Swap et al., 1992) through its long-range transport, and alters the nucleation of clouds and their subsequent precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Second, the vertical transport of (super) coarse dust might be underestimated. In particular, a recent study has shown that topography greatly enhances the upward vertical transport of super coarse dust in the boundary layer (Heisel et al., 2021 ). This effect is not fully accounted for in most models and could help explain the remaining slight underestimation of super coarse dust near source regions (Figures 1b and 2 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Second, the vertical transport of (super) coarse dust might be underestimated. In particular, a recent study has shown that topography greatly enhances the upward vertical transport of super coarse dust in the boundary layer (Heisel et al., 2021 ). This effect is not fully accounted for in most models and could help explain the remaining slight underestimation of super coarse dust near source regions (Figures 1b and 2 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In these schemes the nonlocal eddy diffusivity represents turbulent properties characteristic of the PBL. Models may underestimate the altitude of coarse particles in the PBL, i.e., before they are subject to long-range transport, due to limitations in PBL mixing schemes and/or the omission of phenomena such as the effect of subgrid scale topography upon their vertical mixing (e.g., Rosenberg et al, 2014;Heisel et al, 2021). This could be the case, e.g., for the very deep mixing layer over the Sahara in summer (Garcia-Carreras et al, 2015).…”
Section: Turbulencementioning
confidence: 99%
“…Consequently, aircraft measurements indicate that topography can strongly enhance the vertical transport of super-coarse and (especially) giant dust particles (Rosenberg et al, 2014). Large Eddy Simulations confirm this finding and indicate that the enhanced vertical transport of super-coarse and giant dust occurs because of a number of factors, including upward flow on the uphill slope driving vertical transport and increased vertical dispersion in the wake of crests (Heisel et al, 2021). Most of these processes affecting the emission and vertical transport of super-coarse and giant dust are not represented in current model parameterizations of dust emission, which likely underestimate the emission of super-coarse dust (Huang et al, 2021;Kok et al, 2021a), although an updated parameterization of the emitted dust size distribution using brittle material fragmentation seems to at least partially resolve this problem (Meng et al, 2022).…”
Section: Limitations In Modeling Emission Of Coarse and Super-coarse ...mentioning
confidence: 80%
“…In these schemes the non-local eddy diffusivity represents turbulent properties characteristic of the PBL. Models may underestimate the altitude of coarse particles in the PBL, i.e., before they are subject to long-range transport, due to limitations in PBL mixing schemes and/or the omission of phenomena such as the effect of subgrid-scale topography upon their vertical mixing (e.g., Rosenberg et al, 2014;Heisel et al, 2021). This could be the case, e.g., for the very deep mixing layer over the Sahara in summer (Garcia-Carreras et al, 2015).…”
Section: Turbulencementioning
confidence: 99%